A Very Simple Method for Detection of Bisphenol A in Environmental Water by Heme Signal Amplification. Issue 6 (19th March 2020) - Feng, Xiao-Zhen; Li, Huifang; Ferranco, Annaleizle; Chen, Zhencheng; Xue, Mingyue; Han, Guo-Cheng; Jiang, Zhiliang; Kraatz, Heinz-Bernhard
Abstract : The detection of bisphenol A (BPA) was carried out using several simplified electrochemical sensors in which electroactive materials Heme, dopamine (DA), β -cyclodextrins ( β -CD) or Fc-ECG were deposited on screen-printed electrodes (SPEs) through one-step. The preparation of the developed sensors were verified by SEM, CV and DPV. Results shown that Heme/SPE sensor demonstrated notable electro-catalytic capabilities and a greater current response than other sensors for BPA detection and optimal operating conditions were determined. The current response vs concentration of BPA showed a linear relationship in the range of 0.05–0.50 μ mol·l −1, the concentration limit of detection (S/N = 3) as 5.0 nmol·l −1 and 0.0013 μ A· μ M −1 ·cm −2 as the sensitivity of detection. There were no interferences arising from common elements that relate to BPA. Heme/SPE was applied for BPA detection in bottle drinking water, tap water and lake water; findings showed a total R.S.D. of less than 3.1% and average recovery from 95.0 to 104.0%. These results showed that the actual application of BPA detection was rapid and precise when placed in environmental water and even useful for safety verification.